Solar magnetic flux rope identification with GUITAR: GUI for Tracking and Analysing flux Ropes - Wagner, Andreas; Price, Daniel J.; Bourgeois, Slava; Pomoell, Jens; Poedts, Stefaan; Kilpua, Emilia K. J. (Frontiers in Astronomy and Space Sciences, 2024)
Modelling the early evolution of magnetic flux ropes (MFRs) in the solar atmosphere is crucial for understanding their destabilization and eruption mechanism. Identifying the relevant magnetic field lines in simulation data, however, is not straightforward. In previous work an extraction and tracking method was developed to facilitate this task. Here, we present the corresponding graphical user interface (GUI), called GUITAR (GUI for Tracking and Analysing flux Ropes), with the aim to offer a variety of tools to the community for identifying and tracking MFRs. The starting point is a map of a selected proxy parameter for MFRs, e.g., a map of the twist-parameter T w , magnetic flux density, etc. We showcase how the GUITAR tools can be used to disentangle a multi-MFR system and facilitate in-depth analysis of their properties and evolution by applying them on a time-dependent data-driven magnetofrictional model (TMFM) simulation of solar active region AR12473. We show the MFR extraction using T w maps, together with targeted use of mathematical morphology algorithms and discuss the evolution of the system.